Efficiency Analysis Of Material Management On The Construction Contract Value Of School Buildings In Surabaya - Nurdiyanton, Nurdiyanton; Wulandari , Esti; Purnama, Jaka (Jurnal Teknik Indonesia, 2025)
The development and competition in the world of contractors is very tight, for that a real breakthrough is needed in budget efficiency, namely by managing it well. To realize the perfection and optimization of the company is done with three events, namely time management, cost management and material management. In this case, it is focused on material management, how much influence it has on the performance of the implementation of work in the construction of school buildings in Surabaya. This study was conducted on the construction of buildings, especially school buildings, because school buildings are classified as unique, namely in general the design and structure of the building are typical, starting from the first floor and so on, this can be done by saving materials so that spending can be reduced. The following regression conclusions are obtained: Y1 = 1,360+0,187 +0,425 -0,124 +0,402 -0,190 -0,097 , where the constant value is 1.360 and the variables , , have a positive (+) value, meaning that if the variable is carried out, it will have a positive impact of the value inherent in the equation, conversely , , have a negative (-) value, meaning that if the variable is not carried out, it will have a negative impact on performance of the value inherent in the variable. Thus, the value of efficiency obtained in material management against the contract value is 3% to 5% of the contract value. This can be said to be quite large considering the contract value of each project varies, it will not be felt if the contract value is small.